Infestation Rate of the Coffee Berry Borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae) in South India - Melally Giddegowda Venkatesha; Rudramuni Kiran (Jurnal Proteksi Tanaman)
The coffee berry borer (CBB), Hypothenemus hampei, is a monophagous insect pest that poses a major threat to coffee production worldwide, causing yield losses of up to 30-50%. India's coffee heartland in the south, responsible for over 90% of the national output, grapples with the threat of CBB infestations. Despite its economic importance and global spread, research on the ecology of CBB in India's traditional coffee-growing regions still needs to be completed. In this study, we investigated the infestation rate of CBB in Coffea arabica and C. canephora plantations at three designated locations at Chikkamagaluru (Karnataka), Thandigudi (Tamil Nadu) and Chundale (Kerala) from south India and samplings was done once a month during three fruiting periods between 2015 and 2018. The three sampled sites showed variable percentages of infestation rates across the sampling period between 4.61±0.73 and 29.60±2.28, with the lowest and highest infestation rates in Thandigudi and Chikkamagaluru, respectively. The increase in CBB infestation towards harvest and variations in pre-brood, brood, and post-brood populations suggest the influence of different stages of fresh coffee berries, favorable agro-climatic conditions, and gaps in management strategies in the three sampled regions.